2001
DOI: 10.1520/jfs14906j
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Microscopic Changes Observed at the Human Head Hair Proximal End

Abstract: Only two types of human hair roots (proximal ends) derived from decomposing scalps are reported in the literature. The most common representation of the putrid root includes a postmortem dark root band in published photomicrographs. In this study, 22 cases were reviewed in which there was reliable time of death documentation from medical investigator reports. A review of these cases finds that the most common putrid hair proximal end change does not contain the postmortem root band. Four primary types of hair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(55 citation statements)
references
References 5 publications
9
44
0
Order By: Relevance
“…Overall, Domzalski's work showed that less keratinized layers of the hair root are more susceptible to degradation compared with fully keratinized layers (this finding was initially reported by Petraco et al ), and that humid and aqueous conditions exhibited strong positive correlations with hair root band formation. In agreement with the experiments described by Linch and Prahlow , ambient air alone does not lead to advanced decompositional changes in ex situ antemortem head hairs. Domzalski reported that antemortem root banding (AMRB) can be observed in ex situ head hair samples exposed to certain environments.…”
Section: Temperaturesupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, Domzalski's work showed that less keratinized layers of the hair root are more susceptible to degradation compared with fully keratinized layers (this finding was initially reported by Petraco et al ), and that humid and aqueous conditions exhibited strong positive correlations with hair root band formation. In agreement with the experiments described by Linch and Prahlow , ambient air alone does not lead to advanced decompositional changes in ex situ antemortem head hairs. Domzalski reported that antemortem root banding (AMRB) can be observed in ex situ head hair samples exposed to certain environments.…”
Section: Temperaturesupporting
confidence: 92%
“…The frequency of hair sampling for microscopical analyses and the type of mounting medium used were not provided. No apparent changes were observed for any of the hairs examined . These results suggest that ambient conditions alone do not lead to advanced decompositional changes in ex situ antemortem head hairs.…”
Section: Temperaturementioning
confidence: 60%
See 1 more Smart Citation
“…Currently, there is very limited scientific information available regarding the process of sebaceous gland and hair follicle degeneration. 10 Further studies are required to evaluate these changes and characterize the postmortem changes. The study is limited by the small sample size and evaluation of skin changes in a common environmental setting.…”
Section: Discussionmentioning
confidence: 99%
“…The preferential invasion of anagen and catagen roots is attributed to these roots being softer and more easily degraded, unlike telogen roots that are bulbous and hardened through the keratinization process [34]. Although the precise mechanism responsible for PMB of hairs remains unknown, Linch & Prahlow [35] suggest that microbial and autolytic activities may be of importance.…”
Section: (F ) Keratinolytic Bacterial Invasion Of Hair Shaftsmentioning
confidence: 99%